The entropy vector : connecting science and business - Handscombe, Robert D. (World Scientific, 2004)
How do managers and entrepreneurs evaluate risk, encourage creativityor manage change? Might a better grasp of science help? The authorsof this book suggest that there is real value in trying to connectscience to business and that science is far too important just to beleft to the scientists.